Phase-Shift Control of the Exchange Coupling Between Magnetic Impurities - Altbir-Drullinsky, D; Retamal-Abarzua, J (IOP Publishing Ltd, 2020)
The control of magnetic interactions is one of the most relevant topics in spintronics. In this work, we propose to use electric potential barriers for tuning or even suppressing the RKKY exchange coupling between magnetic impurities in a two-dimensional electron gas. Our results show that it is possible to manipulate both the magnitude and sign of the RKKY coupling. Systems with two and three impurities are studied. In the last case, the use of two potential barriers can be employed to decouple one of the impurities to the rest. The possibility to control the interactions between magnetic atoms individually may have applications in neuromorphic and quantum computing. © 2020 IOP Publishing Ltd.